2018
DOI: 10.1002/pro.3405
|View full text |Cite
|
Sign up to set email alerts
|

p53 promotes its own polyubiquitination by enhancing the HDM2 and HDMX interaction

Abstract: HDM2 and HDMX are two homologs essential for controlling p53 tumor suppressor activity under normal conditions. Both proteins bind different sites on the p53 N-terminus, and while HDM2 has E3 ubiquitin ligase activity towards p53, HDMX does not. Nevertheless, HDMX is required for p53 polyubiquitination and degradation, but the underlying molecular mechanism remains unclear. Alone, HDMX and HDM2 interact via their respective C-terminal RING domains but here we show that the presence of p53 induces an N-terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 31 publications
1
17
0
1
Order By: Relevance
“…The Spearman analysis shows that p53 is strongly correlated with MDM2 and MDMX, which is not surprising since one of the first genes transcribed for p53 is MDM2. Additionally, MDMX and MDM2 are responsible for p53 protein degradation [17]. RB and p53 are also strongly correlated, and it has been shown that RB -/RBmice die during the embryonic stages of the development [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Spearman analysis shows that p53 is strongly correlated with MDM2 and MDMX, which is not surprising since one of the first genes transcribed for p53 is MDM2. Additionally, MDMX and MDM2 are responsible for p53 protein degradation [17]. RB and p53 are also strongly correlated, and it has been shown that RB -/RBmice die during the embryonic stages of the development [25].…”
Section: Discussionmentioning
confidence: 99%
“…MDM2 is a ubiquitin ligase that, under normal cellular conditions, can ubiquitinate and degrade p53 via the proteasome 26S [16]. The MDM2-homologous protein MDMX shares high identity with MDM2, and despite this protein lacking ligase activity it binds p53 and MDM2 to aid in the p53 polyubiquitination process [17]. Retina precursor cells deficient in the RB gene suffers p53-dependent apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…The stability of p53 is determined by the RING domain E3 ubiquitin ligases Mdm2, Pirh2 and COP1 [41,42]. Particularly, Mouse Double Minute 2 (MDM2) is often overexpressed in various types of cancer, inducing proteasome-mediated degradation of p53, thus endorsing cell survival and proliferation [43][44][45]. UBE4B also interacts with MDM2 and is essential for MDM2-mediated p53 poly-ubiquitination and degradation.…”
Section: Ubiquitination and Ubiquitin Proteasome Systemmentioning
confidence: 99%
“…Neskôr boli identifikované aj interakcie ďalších domén vedúcich k ovplyvneniu transkripčnej aktivity proteínu p53, a to kyslej domény HDM2 a DNA-väzbovej domény p53 [11,12] a taktiež kyslej domény HDMX a DNA-väzbovej domény p53, čo vedie k inhibícii väzby p53 k DNA [13]. Interakcia HDM2-HDMX--p53 je veľmi komplexná a je závislá na alosterických zmenách všetkých troch proteínov [14].…”
Section: Funkcia Proteínov Hdm2 a Hdmxunclassified